Performance of HNO3-Activated Water Hyacinth-Eichhornia crassipes Bioadsorbent in Adsorbing Lead Metal Ions (Pb2+) in Battery Industry Wastewater Discharge - Aldiansyah, Wildan; Sari, Dessy Agustina; Wahyuningtyas, Aulia (Journal of Chemical Process Engineering, 2023)
Elemental lead is one of the pollutants generated from batteries. To overcome this problem, technologies such as the use of bioadsorbents have been developed to reduce heavy metal content in wastewater. This study aims to determine the adsorption of lead metal ions (Pb2+) through the use of a water hyacinth (Eichhornia crassipe) bioadsorbent activated with nitric acid (HNO3). Another objective is to obtain the optimum adsorption time on battery industry waste discharges. Post-treatment characterization using FT-IR. Contact time variations (20, 30, 40, 50, 60, 70, 140, 210, and 280 minutes) were used to carry out the lead metal adsorption process on a standard solution of metal ions (Pb2+), 20 ppm. The results showed that the optimum contact time was 210 minutes. This achievement was used as the contact time for reducing the levels of Pb2+ metal ions. The quantity of the remaining Pb2+ metal ion content was 0.4184 ppm. Indirectly, the bioadsorbent performance was 94.8655%. Characterization through FT-IR equipment before activation of water hyacinth bioadsorbent gave results of O-H, C-H, C=O, and C-HO functional groups. These findings indicated the presence of lignin, hemicellulose, and cellulose compounds in the sample before activation. Then, the involvement of 1 N HNO3 solution (as an activator) resulted in a decrease in the quantity of C=O and C-OH functional groups. The process of applying the solution was able to break a number of chains between lignin and hemicellulose. After the adsorption process was given, the waste left the vibrations of O-H, C-H, and ≡C-H groups at wave numbers shifted in a smaller direction. This can occur due to changes in functional groups that have bound metal ions first.